Montenegró és Európa – az integrációs folyamat kérdőjelei - Pap, Norbert; Kitanics, Máté (Közép-Európai Közlemények, 2013)
The fragmentation of the Montenegrin society is significant, in terms of identities, ethnic groups and political values as well. However, the subsidized nature of the alternative of joining the EU is significant and almost unified, which can not be stated in the case of the NATO membership at all. The above mentioned fragmentation goes also with strong political division but the internal conflicts of the past 20 years have not led to violent occurrences, civil war, which can be considered a remarkable phenomenon among the Western-Balkan relations. The country is characterized by organized crime, nepotism, the presence of clan-like phenomena, corruption and the underdevelopment of democratic culture. Among the tasks of Montenegro regarding its accession to the EU, besides strengthening the jurisdiction, reducing the political nature of the administration, the fight againstorganized crime and in this context the elimination of the extensive corruption are prominently included.